The Role and Function of Myths for Religion in Everyday Life - Aulia Diana Devi; Roibin Roibin (UIN Syarif Hidayatullah Jakarta, 2023)
The purpose of this study is to explain the role and function of itos for religion in everyday life. Research methods used with a literature study approach through literature sources from various literature sources about the role and function of myths. Then analyzed and presented the results of the data findings objectively. The results showed that myth is a sacred saying believed by adherents of the myth. A myth usually tells the story of the creation of the universe, the gods, demigods and so on. The values contained in mythical stories are used as guidelines by the community of adherents. There are several types of mythical forms, namely cosmogony myths, origin myths, myths of gods, androgynous myths, and myths of the end of the world. In relation to religion, myths have a very important role. A myth is a story told to establish a particular belief, act as a novice event in a ceremony or rite, or as a fixed model of social or religious behavior. The main and essential functions of the myth are to justify magical acts, as a practical guide in dealing with and relating to the supernatural. In religious life, man will always use a myth to strengthen his belief in the Most High.